Patient Legal Protection Against Pharmacists Negligence in Drug Information Services at Pharmacies: Patient Legal Protection Against Pharmacists Negligence in Drug Information Services at Pharmacies - Ni Made Witari Dewi (Universitas Bali Dwipa, 2022)
Legal protection for patients due to negligence of pharmacists in providing drug information at pharmacies has received less attention because patients consider errors in providing drug information cannot be legally sued. Regulation of the Minister of Health Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies explains that pharmacists when handing over drugs to patients are accompanied by the provision of drug information. Patients are consumers who consume goods and or services from pharmacists in the form of drugs. Law Number 8 of 1999 concerning Consumer Protection explains that consumers have the right to correct, clear, and honest information regarding the conditions and guarantees of goods and/or services. So the researchers focused on the problem, namely what is the form of legal protection for patients against pharmacist negligence in drug information services at pharmacies? and how to solve problems between patients and pharmacists in drug information services at pharmacies?. The method used in this study is a normative research method and the problem approach used is the applicable law approach and the conceptual approach. The results of the discussion found that the forms of legal protection that can be taken by patients are preventive legal protection and repressive legal protection. Legal remedies that can be taken by patients are through mediation, if the mediation is not resolved, then the patient can sue the pharmacist in court or out of court.